Competition and Collusion in Dealer Markets - Dutta, Prajit K.; Madhavan, Ananth (Journal of Finance, 1997)
This article develops a game-theoretic model to analyze market makers' intertemporal pricing strategies. We show that dealers who adopt noncooperative pricing strategies may set bid-ask spreads above competitive levels. This form of “implicit collusion” differs from explicit collusion, where dealers cooperate to fix prices. Price discreteness or asymmetric information are not required for collusion to occur. Rather, institutional arrangements that restrict access to the order flow are important determinants of the ability to collude because they reduce dealers' incentives to compete on price. Public policy efforts to increase interdealer competition should focus on such restrictions.